COMPARATIVE EFFICАCY AND TOLERABILITY OF MONOTHERAPY WITH DEPAKINE CHRONOSPHERE, DRUGS OF CARBAMAZEPINE GROUP WITH EXTENDED RELEASE AND OXCARBAZEPINE IN SYMPTOMATIC AND CRYPTOGENIC FOCAL EPILEPSY (SVT. LUKA’S INSTITUTE OF CHILD NEUROLOGY AND EPILEPSY) - K. Yu. Mukhin; O. A. Pylaeva; R. A. Borodin; L. N. Mukhina (Русский журнал детской неврологии, 2015)
Research on comparative efficаcy and tolerability of monotherapy with Depakine chronosphere, drugs of Carbamazepine group with extended release and oxcarbazepine in symptomatic and cryptogenic focal epilepsy has been conducted at Svt. Luka’s Institute of Child Neurology and Epilepsy (ICNE) (Moscow). This retrospective study covers a random sample of patients treated in ICNE in the period from December 1, 2013 to September 1, 2014.  The study included 131 patients aged 1 to 18 years with symptomatic and cryptogenic focal epilepsy receiving treatment with one of the study drugs in monotherapy: group 1 – monotherapy with Depakine chronosphere (n = 56); group 2 – monotherapy with drugs of carbamazepine group with extended release (n = 55); group 3 – monotherapy with oxcarbazepine (trileptal) (n = 20). The obtained results allow us to conclude that the effectiveness of Depakin chronosphere, carbamazepine with extended release and oxcarbazepine in monotherapy of symptomatic and cryptogenic focal epilepsy was comparable (statistically significant differences in efficacy were not found). However, carbamazepine was awarded the highest frequency of seizures aggravation. Drugs showed approximately same tolerability (statistically significant differences in tolerability were not found). However, withdrawal of the drug due to side effects was the rarest in Depakine (3.5 %), and withdrawal due to intolerance was higher in carbamazepine and oxcarbazepine (5 and 10 % respectively). Depakinum and oxcarbazepine had the best results in the blocking of pathological activity on the electroencephalogram, whereas carbamazepine was clearly inferior to them. In this regard, complete clinical-electroencephalographic remission (lasting 12 months or more) was achieved under treatment of Depakine chromosphere in 21.5 % of cases, oxcarbazepi on therapy for 12 months was similar in all study drugs. Considering that the objective of epilepsy treatment is to achieve complete control over seizures, or at least substantially reduce and weaken them in the absence of significant side effects that disturb the patient’s quality of life, it can be concluded that the best treatment results were obtained in group of depakine chronosphere therapy.